Opto-electronic Properties of Small ZnO\(_2\) Nanoparticles: First-Principles Insights - Tien, Nguyen Thanh; Triet, Dang Minh; Thao, Pham Thi Bich (Communications in Physics, 2022)
We performed density functional theory based first-principles calculations to investigate the opto-electronic properties of small ZnO2 nanoparticles. We have shown that these ZnO2 nanoparticles can exhibit either semiconductor or metallic properties depending on the morphology and sizes of the nanoparticles defined by Miller indices. The absorption spectra computed from the real and imaginary parts of the dielectric functions demonstrate that these nanoparticles exhibit rich optical features with highly spatial anisotropy in the visible light range, suggesting that these newly obtained configurations strongly influence the electronic structures of ZnO2 nanoparticles. Our results propose the potential application of using Zinc peroxide nanoparicles as prospective building blocks for developing early diagnosis nanodevices in drug industry.